Energy-Efficient MU-Massive-MIMO Hybrid Precoder Design: Low-Resolution Phase Shifters and Digital-to-Analog Converters for 2D Antenna Array Structures - Mahmood, Mobeen; Koc, Asil; Le-Ngoc, Tho (IEEE open journal of the Communications Society, 2021)
This paper investigates a multi-user massive multiple-input multiple-output (MU-mMIMO) hybrid precoding (HP) scheme using low-resolution phase shifters (PSs) and digital-to-analog converters (DACs). The proposed HP approach involves two stages: RF beamforming based on the slowly time-varying channel second-order correlation matrix, and baseband MU precoding based on the instantaneous effective baseband channel to mitigate MU-interference by a regularized zero-forcing (RZF) technique. We consider three HP design architectures: (i) HP using full-resolution PSs and DACs, with a baseband transfer block for constant-modulus RF beamformer, (ii) HP using b -bit PSs and full-resolution DACs, with an orthogonal matching pursuit (OMP) based algorithm that can approach the optimal unconstrained RF beamformer, and (iii) HP using b -bit PSs and q -bit DACs, taking into account also DAC quantization noise. Illustrative results show that the proposed HP schemes with low-resolution PSs can approach the sum-rate of full-resolution PSs by using only 2-bit PSs, while offering higher energy efficiency. Furthermore, a study of sum-rate results for various PS and DAC quantization levels reveals that HP can achieve near-optimal performance with only 2-bit PSs and 5-bit DACs. Moreover, a comparison of the different array configurations, namely, uniform linear array (ULA), uniform circular array (UCA), uniform rectangular array (URA), and concentric circular array (CCA), indicates that URA and CCA outperform UCA and ULA in terms of spectral and energy efficiencies.